La promotion de l'équité en éducation sexuelle dans les écoles secondaires de la région d'Ottawa - Martinez, Andrea; Phillips, Karen (Canadian Journal of Education/Revue canadienne de l'éducation, 2009)
Cet article examine les représentations sociales de l’équité en santé sexuelle à partir de données d’entrevues auprès de 30 enseignantes et enseignants des écoles secondaires de la région d’Ottawa, incluant cinq municipalités périphériques de l’est et du centre‐est ontariens.Partant d’un cadre d’interprétation féministe des principaux écueils des interventions en éducation sexuelle, notamment l’âgisme, le naturalisme, l’essentialisme, l’hétérosexisme et l’ethnocentrisme, l’analyse révèle l’omniprésence d’une conception biomédicale de la sexualité qui, nourrie par l’imaginaire du risque, parvient difficilement à rompre les résistances en matière de plaisir, d’autoérotisme et d’intégration des différences sexuelles, « raciales » ou ethniques.
https://journals.sfu.ca/cje/index.php/cje-rce/article/view/3035/2323
Keywords: 2000 à aujourd'hui; 2000-2009; EDI; amérique du nord; amériques; approches et analyses; canada; discipline; hétérosexisme; ontario; ottawa; périodes historiques; ressource en ligne; régions géographiques; santé; santé sexuelle; science de l'éducation; sexualité; systèmes d'oppressions; thématiques; éducation sexuelle; étude qualitative

Ni homme ni femme: enquête sur l'intersexuation - Picquart, Julien (La Musardine, 2009)
"Ni homme ni femme est le premier livre, en français et destiné au grand public, à faire le point sur une question quasiment taboue et presque inconnue de la plupart d'entre nous : comment vit-on avec des organes génitaux atypiques ? Pour y répondre, Julien Picquart a rassemblé des témoignages inédits sur le sujet. Quinze personnes racontent leur quotidien, leur parcours, leur vie sentimentale et sexuelle, les traitements hormonaux et chirurgicaux. Les parents témoignent aussi et reviennent sur leurs réactions quand ils ont découvert que leur enfant n'était pas comme les autres. Pour la première fois également, des médecins parlent, de leurs certitudes et de leurs doutes. Toutes ces personnes nous confrontent à leurs interrogations : faut-il ou non opérer ? N'y a-t-il vraiment que deux sexes ? Quelle importance doit-on accorder aux organes génitaux ? Jusqu'où peut aller notre tolérance ? Un ouvrage accessible et profondément humain, qui bouleverse nos certitudes."
Section: 234 pages, 1 page non numérotée ; 19 cm
Keywords: 1900-1999; 1980-1989; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; premier cycle; périodes historiques; régions géographiques; santé; shm4000; systèmes d'oppressions; thématiques; violences

The Role of Gender and Ethnicity in Perceptions of Rape and Its Aftereffects - Schneider, Lawrence J.; Mori, Lisa T.; Lambert, Paul L.; Wong, Anna O. (Sex Roles : A Journal of Research, 2009)
Caucasian-, Hispanic-, and Asian-American male and female students (n = 764) attending a California (USA) public university reported their perceptions of sexual assault. After reading a rape vignette, participants gave their impressions of the victim; estimated time needed for recovery and treatment; and recommended a sentence for the assailant. Half of the sample received information regarding state sentencing guidelines. Relative to female participants, males perceived the victim as more responsible. Caucasian-American males had stronger reservation about the victim’s judgment. Males were less inclined to assign blame than were females. Ethnicity was the only factor influencing perceptions of recovery. Ethnicity and sentencing guidelines, but not gender, impacted imprisonment decisions. Issues impeding a unified theoretical understanding of perceptions of rape victims were considered.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; californie; cours; discipline; intersectionnalité; perception; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; thématiques; viol; violences; états-unis

Women, gender equality and climate change - United Nations (2009)
Detrimental effects of climate change can be felt in the short-term through natural hazards, such as landslides, floods and hurricanes; and in the long-term, through more gradual deg radation of the environment. The adverse ef fects of these events are already felt in many areas, including in relation to, inter alia, ag riculture and food security; biodiversity and ecosystems; water resources; human health; human settlements and migration patterns; and energy, transport and industry. In many of these contexts, women are more vulnerable to the effects of climate change than men—primarily as they constitute the majority of the world’s poor and are more dependent for their livelihood on natural re sources that are threatened by climate change. Furthermore, they face social, economic and political barriers that limit their coping ca pacity. Women and men in rural areas in developing countries are especially vulnerable when they are highly dependent on local natural resources for their livelihood. Those charged with the responsibility to secure water, food and fuel for cooking and heating face the greatest challenges. Secondly, when coupled with unequal access to resources and to decision-making processes, limited mobility places women in rural areas in a position where they are disproportionately affected by climate change. It is thus important to identify gender-sensitive strategies to respond to the environmental and humanitarian crises caused by climate change.1
Keywords: 2000 à aujourd'hui; 2000-2009; changements climatiques; discipline; droit; développement international; environnement; femmes agricultrices; projet charge mentale; périodes historiques; santé; science politique et droit; sécurité alimentaire; thématiques; travail

Exploration of romantic relationships in adolescent females - Wisnieski, Deborah (The University of Oklahoma, 2009)
Adolescence is a time to explore and develop romantic relationships. Glamorized sexual messages and images bombard youth as they struggle to develop their sexual identity. The darker side of romance that includes teen pregnancy, STDs, and emotional pain is rarely portrayed. Because adolescent females shoulder the burden of unwanted sexual outcomes, an exploration of their experiences, both positive and negative, is the focus of this study. Current literature contains demographic information about who is at risk for unwanted pregnancies and Sexually Transmitted Diseases (STDs), but little is known from the adolescent females’ perspective, about their sexual experiences and even less about normal romantic ideation which drives sexual behavior. This qualitative study utilized ethnographic interviews to explore the experiences of 28 females ages 19-29 from four cultural backgrounds including Euro-American, African-American, American Indian, and Latina. The influence of families, peers, school, and sex education programs was explored for positive and negative experiences. Advice about romantic development to younger adolescent females was sought to gain insight into their development and how to better assist adolescent females in developing healthy romantic relationships. A multi-staged data analysis of the interviews was used to find similarities and differences among the subjects and cross culturally. Discussion of romantic behavior occurred in less than half of the nuclear families. Extended family such as aunts, uncles, and grandparents were named as significant role models by most participants and were frequently described as sources for support and occasionally available for discussion of romantic relationships. Peers were perceived to be sexually active and most behaved in a similar manner. Euro- and African-Americans placed more importance on peer groups. Reproduction was most frequently learned in the school system, rather than from family and peers. The programs were reported as woefully lacking in comprehensiveness. This study calls for policymakers to fund sex education programs for adolescents with potential participation from parents, extended family, and peers. The curriculum should address age-appropriate strategies for discussing romantic and sexual behavior. Additionally, guidelines for monitoring activities and use of new technologies that pose higher risks in early adolescence are most important. Health educators and healthcare providers can utilize these strategies when working with adolescents, families, and peers to improve their romantic relationships and decrease teen pregnancies and STDs.
Keywords: 2000 à aujourd'hui; 2000-2009; adolescentes*; amériques; discipline; mémoires/thèses; philosophie; périodes historiques; relations amoureuses; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexualité; thématiques; états-unis; étude qualitative